2011
DOI: 10.1097/bot.0b013e318234d479
|View full text |Cite
|
Sign up to set email alerts
|

Early Surgical Stabilization of Flail Chest With Locked Plate Fixation

Abstract: This study demonstrates the potential benefits of surgical stabilization of flail chest with locked plate fixation. When compared with case-matched controls, operatively managed patients demonstrated improved clinical outcomes. Locked plate fixation seems to be safe as no complications associated with hardware failure, plate prominence, wound infection, or nonunion were noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 30 publications
6
80
1
3
Order By: Relevance
“…What is more astounding, however, is how our outcomes compare with previously published outcomes in nonoperative patients. 6,[8][9][10][11][12][14][15][16][17][18][19][20] When compared with the RCT by Marasco and colleagues, days on a ventilator in our study were less than half of theirs, ICU LOS in our study was more than 11 days shorter, and hospital LOS was 9 days shorter, while their pneumonia rates were 3 times higher than ours. 10 Despite our retrospective matched cohort design, our study raises some interesting questions for future examination, especially considering that the only other North American study on this topic also found no significant improvements in LOS or ventilator days with flail chest fixation.…”
Section: Discussioncontrasting
confidence: 37%
“…What is more astounding, however, is how our outcomes compare with previously published outcomes in nonoperative patients. 6,[8][9][10][11][12][14][15][16][17][18][19][20] When compared with the RCT by Marasco and colleagues, days on a ventilator in our study were less than half of theirs, ICU LOS in our study was more than 11 days shorter, and hospital LOS was 9 days shorter, while their pneumonia rates were 3 times higher than ours. 10 Despite our retrospective matched cohort design, our study raises some interesting questions for future examination, especially considering that the only other North American study on this topic also found no significant improvements in LOS or ventilator days with flail chest fixation.…”
Section: Discussioncontrasting
confidence: 37%
“…As compared to nonoperative treatment, patients undergoing rib fixation have been shown to have shorter intensive care unit stays, decreased ventilator requirements, shorter overall hospital length of stays, fewer tracheostomies, less pneumonia, less need for reintubation, and decreased home oxygen supplementation [1,6,8]. However, evidence-based treatment algorithms for rib fracture fixation are currently absent, as further large-scale randomized studies are needed to help further delineate true surgical indications.…”
Section: Discussionmentioning
confidence: 99%
“…Open reduction and internal fixation for rib fractures is an increasingly established treatment method for flail chest [1]. As compared to nonoperative treatment, patients undergoing rib fixation have been shown to have shorter intensive care unit stays, decreased ventilator requirements, shorter overall hospital length of stays, fewer tracheostomies, less pneumonia, less need for reintubation, and decreased home oxygen supplementation [1,6,8].…”
Section: Discussionmentioning
confidence: 99%
“…Different materials and methods involved in surgical fixation for fractured ribs have been reported [16,26,27]. But actually, reliable and effective materials and methods proved by clinical trials are still few.…”
Section: Discussionmentioning
confidence: 99%